2018
DOI: 10.1071/rd17420
|View full text |Cite
|
Sign up to set email alerts
|

CASA: tracking the past and plotting the future

Abstract: The human semen sample carries a wealth of information of varying degrees of accessibility ranging from the traditional visual measures of count and motility to those that need a more computational approach, such as tracking the flagellar waveform. Although computer-aided sperm analysis (CASA) options are becoming more widespread, the gold standard for clinical semen analysis requires trained laboratory staff. In this review we characterise the key attitudes towards the use of CASA and set out areas in which C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 66 publications
0
35
0
1
Order By: Relevance
“…Such systems are widely used for veterinary work and in domestic animal breeding, conservation, and toxicology (Amann and Waberski, 2014), but have not yet made the breakthrough into routine clinical usage. The reasons for this have been discussed elsewhere (Gallagher et al, 2018b).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Such systems are widely used for veterinary work and in domestic animal breeding, conservation, and toxicology (Amann and Waberski, 2014), but have not yet made the breakthrough into routine clinical usage. The reasons for this have been discussed elsewhere (Gallagher et al, 2018b).…”
Section: Introductionmentioning
confidence: 94%
“…The package will be shown to provide positions in time of tracked sperm head and flagellum, and associated measurement of the flagellar arc-wavelength, flagellar beat frequency, and power dissipation by the flagellum in addition to providing the existing CASA measures. FAST is not designed to analyse raw semen, it is specifically for precise analysis of flagellar kinematics, as that is the promising area for computer use (Gallagher et al, 2018b). Flagellar capture will always require that cells are at a dilution where their paths do not frequently cross.…”
Section: Introductionmentioning
confidence: 99%
“…However, the extensive user intervention still required for such packages as well as basic thresholding based techniques, for example by Smith et al [4] who reported on the beats of 36 swimmers, has to date largely restricted population-level computer-assisted sperm analysis (CASA) to head-based investigations [5][6][7][8] and assessments of flagellar morphology [9], with flagellar waveforms neglected. Despite such limitations, and its only partial acceptance in clinical diagnostics [10], CASA has also found extensive application in reproductive toxicology, quality assurance for semen marketing in livestock breeding, improvements in sperm technologies such as cryopreservation, and studies of basic sperm function [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There has long been interest in understanding the mechanics and regulation of sperm flagellar movement, in particular problems relating to: understanding the mechanical struc-ture and motor regulation [5,[12][13][14], investigating the response of the flagellar beat to its rheological environment [15][16][17], understanding the dynamics of sperm due to surrounding solid walls [18,19], and studying the effect of viscosity on sperm swimming [20]. For a detailed review surrounding the importance of the sperm flagellum see Gallagher et al [21]. Furthermore, such a method could be used to investigate phenomena associated with epithelial cilia driven flows such as: cilia waveform modulation by length [5], the effects of flow induced by cilia on embryonic development [22], studying the physical limits of flow sensing [23], and investigating the mechanical structure of the axoneme in cilia [24].…”
Section: Introductionmentioning
confidence: 99%